Carotid sparing intensity-modulated radiation therapy achieves comparable locoregional control to conventional radiotherapy in T1-2N0 laryngeal carcinoma. Issue 7 (July 2015) - Zumsteg, Zachary S.; Riaz, Nadeem; Jaffery, Sana; Hu, Man; Gelblum, Daphna; Zhou, Ying; Mychalczak, Borys; Zelefsky, Michael J.; Wolden, Suzanne; Rao, Shyam; Lee, Nancy Y.
Summary Background Although intensity-modulated radiotherapy (IMRT) is a standard of care for many head and neck cancers, its use for carotid-sparing (CS) therapy in early-stage laryngeal carcinoma is controversial. Methods 330 consecutive patients with early-stage laryngeal carcinoma were treated from 1/1989 to 5/2011, including 282 conventional radiotherapy (CRT) and 48 CS-IMRT patients. The median follow-up was 43 (CS-IMRT) and 66 (CRT) months. Results There was no difference in local failure rates comparing patients undergoing CS-IMRT with CRT, with 3-year local control rates of 88% vs. 89%, respectively (p = 0.938). Using a 1 cm circumferential margin, the average dose to the left and right carotid arteries was 48.3 and 47.9 Gy, respectively. 88% of locoregional recurrences involved the ipsilateral true vocal cord, including all local recurrences in the IMRT group. Conclusions These results warrant further prospective evaluation of CS-IMRT for early-stage glottic larynx cancer.